Analisis Faktor Minat Mahasiswa Pendidikan Ekonomi Untuk Menjadi Guru Melalui Program Pendidikan Profesi Guru - Meta Oktri Astuti; Syamwil Syamwil; Dessi Susanti (Jurnal Ecogen, 2018)
Abstract: The aim of this study is to analyze the interest factor of economic education students to be a teacher through Teacher Professional Education Programs. This study is quantitative descriptive study with using propotional sampling technique. The population in this reseach is 423 students of economic education. Questionnaire is used to collect the data from 81 respondents who know about Teacher Professional Education Programs (PPG) in Economic Education Program in Economic Faculty State University of Padang. The data is collected and analyzed using descriptive and factor analysis. The result of this study show that emotional factor, peer factor, society factor, factor of curiosity, the ability factor, physical factor, and the motive factor are the factor that influence the interest of economic education students to be a teacher through Teacher Professional Education Programs. Based on the result of research, recommended to students majoring in economic education to better understand and add insight into teacher professional education programs by looking for articles and information as well as sosialization from lectures about PPG.Keyword: Economic education program, interest factor, teacher profesional education, emotional, society